Pituitary Adenomas – Clinico-Pathological, Immunohistochemical and Ultrastructural Study - Ortiz-Plata, Alma; Tena-Suck, Martha L.; Pérez-Neri, Iván; Rembao-Bojórquez, Daniel; Fernández, Angeles (IntechOpen, 2012)
None